Current practice of iron prophylaxis in preterm and low birth weight neonates: A survey among Italian Neonatal Units - Emilia Parodi; Anna Ferrero; Barbara Perrone; Paola Saracco; Maria Teresa Giraudo; Daniela Regoli (Pediatrics and Neonatology)
Background: Preterm babies are at high risk of iron deficiency. Methods: We investigated current practices regarding iron prophylaxis in preterm and low birth weight newborns among Local Neonatal Units (LNUs, n = 74) and Neonatal Intensive Care Units (NICUs, n = 20) of three Italian Regions (Piemonte, Marche and Lazio). Results: Birth weight is considered an indicative parameter in only 64% of LNUs and 71% of NICUs, with a significant difference between LNUs in the three regions (86%, 20% and 62%, respectively; p < 0.001). Iron is recommended to infants with a birth weight between 2000 and 2500 g in only 25% of LNUs and 21% of NICUs, and to late-preterm (gestational age between 34 and 37 weeks) in a minority of Units (26% of LNUs, 7% of NICUs). Conclusions: Our pilot survey documents a great variability and the urgent need to standardize practices according to literature recommendations. Key Words: iron, iron deficiency anemia, newborn, preterm, prophylaxis